Eddy-induced sea surface salinity changes in the South China Sea - Yang, Yikai; Guo, Yiming; Zeng, Lili; Wang, Qiang (Frontiers in Marine Science, 2023)
Eddy-induced sea surface salinity (SSS) changes are systematically studied in the South China Sea (SCS) by using Soil Moisture Active Passive (SMAP) satellite salinity data from 2015 to 2021 for the first time. All eddies in the SCS during this period are analysed, and two normalized eddy composites are reconstructed under the long-term basin mean. In general, anticyclonic eddies (AEs) tend to result in lower salinity than cyclonic eddies (CEs) in the upper ocean. The salinity anomalies of the AE and CE composites are dominated by dipole and monopole structures, respectively. The different patterns in eddy-induced salinity anomalies are generally controlled by horizontal and vertical advections, which is further confirmed by their seasonal evolutions. A spatiotemporal decomposition of these salinity anomaly patterns suggests that the dipole and monopole patterns account for more than 70% of the salinity variability. All the eddies in the SCS are monopole-dominated and dipole-supplemented overall. This finding infers a relatively uniform eddy-induced salinity structure across the SCS and provides an observational-based metric for future model studies.